Les TIC et la prospective sur les espaces ruraux : retour sur le programme « territoires 2040 » - Laurence Barthe; Johan Milian (Netcom, 2011)
Territorial foresight is a very convenient tool for policy action and territorial planning. Its practice aims to a better understanding and exploration of current trends and stakes in order to pioneer the future and anticipate main or uncertain evolutions. We expose here the results of a French territorial foresight exercise named Territoires 2040, regarding the links between ICTs topic and landlocked and remote rural areas context. Although ICTs served to settle the initial diagnosis, they have been little taking into account concerning the building of the scenarios. We try to go further, enlightening what part ICTs could have among the process which rule the scenarios of 2040 rural areas.